1996
DOI: 10.1107/s010827019600354x
|View full text |Cite
|
Sign up to set email alerts
|

Diisopropylammonium Bromide

Abstract: (1974, Vol. IV) 1.486 (6) C(I 2)---<2 (13) 1.517 (6) C(12)---C(14)1.526 (6)110.9 Symmetry codes: (i) x, 1 + y, ½,½-z;(iv) x-l,Y,Z. CAMERON (Pearce & Watkin, 1993). Software used to prepare material for publication: CRYSTALS.HRP wishes to thank the CCDC and the University Chemical Laboratories, Cambridge, for the use of X-ray diffraction and computing facilities.Lists of structure factors, anisotropic displacement parameters, Hatom coordinates and complete geometry have been deposited with the IUCr (Referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Initially, the closely related bromine analog, diisopropylammonium bromide (DPB), had seemed to be a good candidate to exhibit polar properties in the room temperature phase, however, further research indicated that the phase situation and a rich polymorphism of DPB appeared to be quite complicated. Two polymorphs of DPB are known at room temperature: monoclinic P2 1 6 and orthorhombic P2 1 2 1 2 1 . 7 The crystal structure of the latter polymorph (abbreviated in this paper as O) was presented as a private communications by G. J. Reiss.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the closely related bromine analog, diisopropylammonium bromide (DPB), had seemed to be a good candidate to exhibit polar properties in the room temperature phase, however, further research indicated that the phase situation and a rich polymorphism of DPB appeared to be quite complicated. Two polymorphs of DPB are known at room temperature: monoclinic P2 1 6 and orthorhombic P2 1 2 1 2 1 . 7 The crystal structure of the latter polymorph (abbreviated in this paper as O) was presented as a private communications by G. J. Reiss.…”
mentioning
confidence: 99%
“…7 The monoclinic polymorph was obtained accidentally during the reaction of BrRe(CO) 5 and lithium diisopropylamide. 6 It undergoes an irreversible PT below room temperature to the monoclinic phase (P2 1 /n). 8 In turn, O presented in this paper was obtained during the reaction of HBr and diisopropylamine and did not disclose any PTs below room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the structural chemistry of simple dipH salts dates back in the ninetys of the last century [18]. The dipH halogenides and some other directly related salt structures, which were characterized, all feature hydrogen bonded chains [19][20][21][22][23][24][25][26][27].…”
Section: Commentmentioning
confidence: 99%
“…It has been reported that diisopropylammonium bromide (DIPAB) crystallizes into a room-temperature ferroelectric phase branded as P2 1 (α-DIPAB) and a high temperature paraelectric phase categorized as P2 1/m (β) [7]. X-ray diffraction (XRD) structural characterization indicates that P2 1 (α-DIPAB) belongs to polar point group C 2 [8] illustrated schematically in Figure 1A. In contrast, at high temperature P2 1/m (β) has a crystal structure with a non-polar point group D 2 shown schematically in Figure 1B.…”
Section: Introductionmentioning
confidence: 99%